MOTIVASI SOSIAL DAN INSENTIF NON-MATERIAL SEBAGAI FAKTOR PENDORONG KINERJA KARYAWAN DI FOURTEEN ROSES BOUTIQUE HOTEL - I Nyoman Widya Saputra; Kadek Devi Kalfika Anggria Wardani (CV. Lafadz Jaya, 2026)
This study is motivated by the importance of improving employee performance in the hospitality industry, which highly depends on psychological and non-financial factors. This study aims to determine the effect of Social Motivation and Non-Material Incentives on Employee Performance at Fourteen Roses Boutique Hotel. The research method used is quantitative with a sample of 59 hotel employees. Data were collected through questionnaires using a Likert scale and analyzed using validity test, reliability test, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination using SPSS version 25. The results show that Social Motivation has a positive and significant effect on Employee Performance with a significance value of 0.006 < 0.05. Non-Material Incentives also have a positive and significant effect on Employee Performance with a significance value of 0.000 < 0.05. Simultaneously, Social Motivation and Non-Material Incentives significantly affect Employee Performance with an F value of 128.066 and a significance value of 0.000 < 0.05, contributing 81.4% to employee performance. The conclusion of this study is that improving employee performance can be achieved by strengthening social motivation and providing appropriate non-material incentives in the workplace.